2010
DOI: 10.1002/pbc.22923
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in childhood leukemia survivors treated with cranial radiotherapy: A cross sectional, single center study

Abstract: These results confirm that total doses and modalities of fractionation dose of CRT were not significantly associated with MRI abnormalities. Moreover, in our experience none of the patients developed neurological symptoms related to MRI abnormalities, and furthermore, the CC remained substantially stable during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
(41 reference statements)
2
17
1
Order By: Relevance
“…[18][19][20][21][22][37][38][39][40][41] In our study, a considerable number of survivors with LE (n = 58/163, 36%) had CNS LE and this is comparable with the study by Smedler et al 22 and one study reported that 11 of 13 (85%) patients transplanted before age 3 with TBI had neuropsychological abnormalities. 11 In the study by Leung et al, 10 two of seven infant leukaemia patients with cranial irradiation (CRT/TBI) and HSCT developed a seizure disorder.…”
Section: Discussionsupporting
confidence: 93%
“…[18][19][20][21][22][37][38][39][40][41] In our study, a considerable number of survivors with LE (n = 58/163, 36%) had CNS LE and this is comparable with the study by Smedler et al 22 and one study reported that 11 of 13 (85%) patients transplanted before age 3 with TBI had neuropsychological abnormalities. 11 In the study by Leung et al, 10 two of seven infant leukaemia patients with cranial irradiation (CRT/TBI) and HSCT developed a seizure disorder.…”
Section: Discussionsupporting
confidence: 93%
“…Others report an inverse relationship, finding that ICMs occur more commonly at the lower dose rim of the radiation field 5, 11 . Regardless, it appears that low+dose radiation is sufficient to induce ICMs, as children with leukemia, who are treated with relatively low doses of radiation (12+24 Gy), are also at increased risk for developing ICMs 11, 12 .…”
Section: Introductionmentioning
confidence: 99%
“…10,13 In a previous study of 6 patients who received cranial irradiation for leukemia (3 patients), pontine glioma (1 patient), MB (1 patient), or cerebellar astrocytoma (1 patient), symptomatic FHDs requiring surgery developed in 3 patients (2 with leukemia and 1 with cerebellar astrocytoma). 16 In our cohort consisting only of RT-treated MB patients, none of the FHDs resulted in symptomatic hemorrhage that required surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since Gaensler et al 11 and Poussaint et al 23 first described the features of the these lesions, an increase in the number of survivors of childhood cancers has resulted in an increase of lesion detection on routine MRI scans. The incidence of these lesions reported in the literature now ranges from 2.6%-57%, 4,10,13,15,17 and its wide range is likely attributable to different diagnostic methods, heterogeneous underlying diseases, and therapies (chemotherapy and radiation field and dose). Studies have suggested a higher incidence of these lesions among children, 13,21 particularly after treatment of MB, 17,21 and this was confirmed in the present study, which showed that 80% of patients treated for MB showed FHDs, 94% of whom had multiple lesions.…”
Section: Discussionmentioning
confidence: 99%